Correlation between Investigative Findings and PerOperative findings of stomach cancer (The Insight, 2024)
Introduction: Stomach cancer remains a major global health challenge, with significant morbidity and mortality rates. Accurate pre-operative assessments are crucial for effective surgical planning and improved patient outcomes. This study aimed to investigate the correlation between pre-operative investigative findings and per-operative observations in patients with stomach cancer. Methods & Materials: This retrospective cohort study analyzed 100 stomach cancer patients at Department of Surgery, Sylhet MAG Osmani Medical College Hospital, Sylhet, from September 2012 to August 2013. It included patients aged 18+ with confirmed diagnoses, focusing on demographic data, clinical presentation, and pre-operative imaging compared to intra-operative findings. Statistical analysis assessed correlation, sensitivity, specificity, PPV, NPV, and potential confounders using SPSS 26. Results: The study revealed that the majority of patients were aged 60 and above (50%), with a higher prevalence in males (60%). Abdominal pain (70%) and weight loss (50%) were the most common symptoms. Pre-operative imaging showed strong correlations with per-operative findings: tumor size (r=0.85, p
Keywords: Stomach Cancer; Gastrointestinal disorders; Per-Operative Findings; Correlation, Surgical Planning